The association of area deprivation and state child health with respiratory outcomes of pediatric patients with cystic fibrosis in the United States. Issue 5 (14th December 2020) - Oates, Gabriela; Rutland, Sarah; Juarez, Lucia; Friedman, Annabelle; Schechter, Michael S.
Abstract: Background: Differences in socioenvironmental exposures influence overall child health, but their association with pediatric cystic fibrosis (CF) outcomes is less clear. This observational study investigated the relationship between area‐level socioeconomic deprivation, state child health, and CF respiratory outcomes in a national cohort. Methods: We assessed relationships between the 2015 area deprivation index, a composite measure of socioeconomic disadvantage; the 2016 child health index, a state‐specific measure of overall child health; and CF respiratory outcomes in the 2016 CF Foundation Patient Registry. Results: The sample included 9934 individuals with CF, aged 6–18 years. In multiple regression analysis adjusted for demographic and clinical covariates, those residing in the worst tertile for area deprivation had 2.8% lower percent predicted forced expiratory volume in 1 s (ppFEV1 ; 95% confidence interval [CI]: −4.1 to −1.5), 1.2 more intravenous (IV) treatment nights (CI: 0.1–2.4), and 20% higher odds of ≥2 pulmonary exacerbations (odds ratio [OR]: 1.2, CI: 1.0–1.5) than best‐tertile counterparts. Children with CF in states at the worst tertile for child health had 2.3% lower ppFEV1 (CI: −4.5 to −0.2), 2.2 more IV treatment nights (CI: 0.5–3.6), and 40% higher odds of ≥2 exacerbations (OR: 1.4, CI: 1.1–1.8) than best‐tertile counterparts. State child health accounted for the association between area deprivation and multiple exacerbations and more IV treatment nights. Conclusions: Both area socioeconomic characteristics and state child health play a role in pediatric CF outcomes. The residual association of the state child health with CF outcomes after controlling for area deprivation reflects the ability of state programs to mitigate the effect of poverty.